Changes in the south Asian monsoon low level jet during recent decades and its role in the monsoon water cycle. (February 2016) - Aneesh, S.; Sijikumar, S.
Abstract: June–September mean wind at 850 hPa from ERA-Interim, MERRA and NCEP2 reanalyses shows an increasing trend in the south Asian monsoon Low Level Jet (LLJ) during 1980–2014. In the sub-seasonal scale, the LLJ during July and September exhibits increasing trend, while August shows a decreasing trend. Lesser changes in surface pressure over heat low region and weaker Bay of Bengal convection lead to weakening of LLJ during August while an intense heat low during September results stronger LLJ. The associated moisture transport changes affect the monsoon hydrological cycle with decreasing precipitation during August and increasing precipitation during September. Highlights: Increasing trend in the south Asian monsoon low level jet (LLJ) during 1980-2014. In subseasonal scale, July and September show increasing trend. The LLJ during August shows a decreasing trend. Enhanced land-sea temperature contrast strengthens the LLJ during September. Strengthening of LLJ in September increases moisture transports and enhanced precipitaton at the end of the season.